The effect of pre-test carbohydrate ingestion on the anaerobic threshold, as determined by the lactate-minimum test - Rotstein, A.; Dotan, R.; Zigel, L.; Greenberg, T.; Benyamini, Y.; Falk, B. (Applied Physiology, Nutrition, and Metabolism, 2007)
The purpose of this study was to investigate the effect of pre-test carbohydrate (CHO) ingestion on anaerobic-threshold assessment using the lactate-minimum test (LMT). Fifteen competitive male distance runners capable of running 10 km in 33.5-43 min were used as subjects. LMT was performed following CHO (2 × 300 mL, 7 % solution) or comparable placebo (Pl) ingestion, in a double-blind, randomized order. The LMT consisted of two high-intensity 1 min treadmill runs (17-21 km·h-1), followed by an 8 min recovery period. Subsequently, subjects performed 5 min running stages, incremented by 0.6 km/h and separated by 1 min blood-sampling intervals. Tests were terminated after 3 consecutive increases in blood-lactate concentration ([La]) had been observed. Finger-tip capillary blood was sampled for [La] and blood-glucose determination 30 min before the test`s onset, during the recovery phase following the 2 high-intensity runs, and following each of the subsequent 5 min stages. Heart rate (HR) and rating of perceived exertion (RPE) were recorded after each stage. The lactate-minimum speed (LMS) was determined from the individual [La]-velocity plots and was considered reflective of the anaerobic threshold. Pre-test CHO ingestion had no effect on LMS (13.19 ± 1.12 km/h vs. 13.17 ± 1.08 km/h in CHO and Pl, respectively), nor on [La] and glucose concentration at that speed, or on HR and RPE responses. Pre-test CHO ingestion therefore does not affect LMS or the LMT-estimated anaerobic threshold.